2014
DOI: 10.1063/1.4896272
|View full text |Cite
|
Sign up to set email alerts
|

Logic-memory device of a mechanical resonator

Abstract: We report multifunctional operation based on the nonlinear dynamics in a single microelectromechanical system (MEMS) resonator. This Letter focuses on a logic-memory device that uses a closed loop control and a nonlinear MEMS resonator in which multiple states coexist. To obtain both logic and memory operations in a MEMS resonator, we examine the nonlinear dynamics with and without control input. Based on both experiments and numerical simulations, we develop a novel device that combines an OR gate and memory … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 26 publications
0
50
0
Order By: Relevance
“…This result is due to the mechanical nonlinearity named spring hardening which is associated with the impact of mechanical restoring force. 18,19 Both the resonators show a similar trend of electrical and mechanical nonlinearity which can be mutually canceled since the device works in the differential sensing scheme. Therefore, the defects of nonlinear behavior such as energy dissipation and resonance instability can be suppressed.…”
mentioning
confidence: 99%
“…This result is due to the mechanical nonlinearity named spring hardening which is associated with the impact of mechanical restoring force. 18,19 Both the resonators show a similar trend of electrical and mechanical nonlinearity which can be mutually canceled since the device works in the differential sensing scheme. Therefore, the defects of nonlinear behavior such as energy dissipation and resonance instability can be suppressed.…”
mentioning
confidence: 99%
“…The hysteresis due to the nonlinearity of the modes also provides a straightforward way to store these logical output states. 10,11 In conclusion, we have shown that two orthogonal flexural modes of a GaAs nanowire can couple through nonlinear terms in the motion. The mode coupling is clearly visible in ringdown measurements, where we observe a beating pattern with frequency equal to the difference in mode frequencies.…”
Section: Nano Lettersmentioning
confidence: 99%
“…7 Furthermore, the coupling of mechanical modes has various applications including in frequency and amplitude modulation, 8 improving mechanical quality factors, 9 in several parametric amplifications schemes, and in the implementation of mechanical logic. 10,11 Mode coupling may also be used in the enhancement of mechanically detected mass, charge, and force sensitivity. 12,13 For these reasons, such coupling has been studied in numerous top-down fabricated nanomechanical systems including single 14,15 and double beam structures 8,16 and membranes.…”
mentioning
confidence: 99%
“…The high structural quality of those materials combined with the reduced effective mass allows such beams to operate at very high resonance frequencies with extremely high Q factors (i.e., low damping). These beneficial attributes provide the basis for exceptional performance of MEMS applications such as extremely sensitive sensors [1][2][3][4], mechanical energy harvesters [5][6][7], nano/micro-relays [8,9], logic memory and computation [10][11][12], field effect transistors [13], and a high frequency reference in oscillators [14][15][16]. The MEMS devices implemented in these applications were mostly designed to operate in their linear resonant modes with the above-mentioned benefits.…”
Section: Introductionmentioning
confidence: 99%